The promised Neverland. 5, Escape - Shirai, Kaiu (Shonen Jump manga., 2018)
"Life at Grace Field House is good for Emma and her fellow orphans. While the daily studying and exams they have to take are tough, their loving caretaker provides them with delicious food and plenty of playtime. But perhaps not everything is as it seems... As Grace Field House goes up in flames, Emma and the other children make their run for freedom. With Mom refusing to give up and an army of demons at her call, this escape from captivity won't be easy. Just what will Emma have to sacrifice to pull it off...?"--Page [4] of cover.